Anti-Inflammatory Activity of Marine Sponge Aaptos sp. to the Plasma Interleukin-1β Level in Wistar Male Rats - Adryan Fristiyohadi; Wahyuni Wahyuni; Wa OIL. Kalimin; La OMJ. Permana; Saripuddin Saripuddin; Idin Sahidin (Pharmacology and Clinical Pharmacy Research)
Inflammation is the response of the body to injury and infection characterized by swelling, heat, pain, and redness. This study aimed to investigate the anti-inflammatory effect of Aaptos sp. ethanolic extract to plasma interleukin (IL)-1β level of Wistar male rats. Aaptos sp. was macerated with 96% ethanol for 3 x 24 hours. Inflammation was induced with administration of 1% carrageenan intraplantarly. Animals were divided into 5 treatment groups, i.e., positive control  (diclofenac sodium 3598 ppm); Aaptos sp extract 50 ppm; Aaptos sp extract 100 ppm Aaptos sp extract 200 ppm; and negative control (0.5% Na CMC). After 1 hour, blood was collected and assayed using enzyme-linked immunosorbent assay (ELISA) kit. The results showed that plasma IL-1β levels of animals were decreased by Aaptos sp ethanolic extract. The administration of 50 ppm of extract showed no significant difference (p>0.05)  in IL-1β level in first and second hour measurement, but indicated a statistically significant decrease after three hour (p<0.05). The administration of 100 ppm of extract showed no significant difference (p>0.05) in every hour. Significant reduction was observed in the administration of 200 ppm of extract, but the elevation of IL-1β levels was also observed at third hour measurement. In conclusion, ethanolic extract of Aaptos sp. had anti-inflammatory activity and its effective dose was 50 ppm.